(untitled) (Journal of the College of Basic Education, 2022)
The study Nakecah writings of important studies in the civilizations of peoples and nations, and through it can reach a long history of these peoples and originality, and The Middle East (Mesopotamia and the Levant and the Arabian Peninsula), the cradle of the oldest human civilizations, particularly Mesopotamia, because it embraced the first civilization in the world and it codified initials at the hands of the Sumerians. The study of literature Nakecah is the best way to see the old and authentic civilization, because the language is a sign of civilization, which is evidence of their existence and one of its components. The Aramaic language of Semitic languages ​​task, come significance being one of the Semitic languages ​​live, and since its discovery is still in circulation to the present day despite the development that took place from the line hand to simplify the process of writing, where he wrote this the product of a huge literature language and some scripts which invited me to study the subject to the content of the linguistic and historical methods, compared with the rest of her sisters from other Semitic languages. The optional study the writings Nakecah in the monastery of Our Lady’s Church (crops portfolio), on the walls and gravestones where due mentioned by travelers and historians. As well as to their importance in the Eastern Church and the effective role which, because it is through the first stages through which, in addition to that the line started by the writings Nakecah type, which is Alostrndjeli line.